Perancangan Sistem Tanggap Darurat Fakultas Teknik Universitas Riau - Ery Laksono Sadewo; Muhammad Reza; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Fires are caused by various factors, but generally the factors that cause fires namely human factors and technical factors. University of Riau is one of the educational institutions in Riau Province where there is a risk of fire. This study aims to evaluate and design emergency response systems and fire protection systems in the Faculty of Engineering Building, University of Riau. In evaluating and designing emergency response systems and fire protection systems the authors use references from Minister of Public Works No.26 / PRT / M / 2008, Permen PU No.20 / PRT / M / 2009, SNI, and use the assessment format of the Public Works Research and Development Agency 2005. The method used in this study is a quantitative descriptive method with a case study design, which compares the results of research in the field with applicable regulations. Based on the results of evaluations that have been carried out, the Emergency Response System of the Faculty of Engineering, University of Riau as a whole has not been fulfilled. The Fire Protection Facilities of the Faculty of Engineering, University of Riau Building are overall sufficient. For this reason, it is necessary to procure and improve the Emergency Response and Fire Protection System of the University of Riau's Faculty of Engineering Building as well as the maintenance of the available systems.Keywords: Fire, Evaluation, Emergency Response System, Fire Protection System